Synergy of tensile strength and ductility in a novel additively manufactured Al-Mg-Mn-Er-Zr alloy with a trilevel equiaxed heterogeneous structure - Jifei Hu; Wu Wei; Shengping Wen; Jianlei Bi; Jieming Gao; Xingkai Hou; Kunyuan Gao; Peng Qi; Tongbo Wang; Xiaorong Zhou; Yuyan Zhai; Xiaocheng Shi; et al. (Virtual and Physical Prototyping)
This study investigates a novel Al-Mg-Mn-Er-Zr alloy with high strength and elongation. The uneven distribution of L12-Al3Er and Al3(Er, Zr) phases in the molten pool structure results in a trilevel equiaxed heterogeneous structure in the alloy. The as-printed alloy exhibits various forms of Al3(Er, Zr) phases and Er-containing primary phases (such as Al3(Zr, Er)5), demonstrating an excellent combination of strength (ultimate tensile strength of 531 MPa, yield strength of 455 MPa) and elongation (fracture elongation of 27%). The strengthening mechanism and strain distribution behaviour of the heterogeneous structure are explored to understand the alloy's elongation and strength mechanism. The large equiaxed grains concentrated in the centre of the molten pool contribute to high elongation, while heterogeneous deformation-induced (HDI) strengthening caused by heterogeneous grains increases the strength. The ultrafine grains at the molten pool boundaries ensure that strength remains at a high level, achieving a good balance of strength and elongation.